(untitled) (Journal of Recent Advances in Applied Sciences (pISSN 0970-1990), 2025)
Introduction: Psychological factors are increasingly recognized as important contributors to dermatological disorders. Many patients with skin diseases experience significant emotional distress, which negatively affects their quality of life and interferes with overall well-being. Symptoms such as anxiety, depression, low self-esteem, and social withdrawal are commonly reported. In addition to psychological variables, socio-demographic factors-including age, gender, marital status, educational level, and socioeconomic status may influence both the onset and prognosis of dermatological conditions. Understanding these associations is essential for guiding patient-centred and holistic management. Aim & Objective: The present study aims to evaluate socio-demographic variables and examine their correlation with psychiatric morbidities among patients with dermatological disorders. Materials & Methods: This hospital-based prospective study was conducted among patients attending the outpatient department (OPD) and inpatient ward of the Dermatology Department at B. S. Kushwah Medical College, Kanpur. Relevant socio-demographic information, along with psychiatric symptoms and diagnoses, was systematically assessed. Results: The findings demonstrate that gender, age, educational level, and socioeconomic status significantly influence the prevalence of psychiatric morbidities in dermatological patients. A statistically significant association was observed in married females, individuals aged 41–60 years, and those with education below the high-school level, who exhibited higher rates of psychiatric comorbidities compared to other groups. Conclusion: This study underscores the strong relationship between socio-demographic characteristics and psychiatric morbidities in patients with dermatological disorders. As individuals presenting to hospitals are more likely to have moderate to severe disease, these findings may not fully represent the general population of dermatology patients. Integrating psychological assessment and support into dermatological care may improve overall treatment outcomes and enhance quality of life.